COVID-19 Booster Vaccine: is it an absolute need? - Ghimire, S.; Dangal, G. (Kathmandu University Medical Journal, 2021)
Booster vaccine doses are meant to revive the fading immunity created by prior exposure to an immunizing antigen. They stabilize the antibody response ultimately leading to longer and higher protection against pathogens. Immunological studies done for COVID-19 vaccines have documented a steady decrease in antibody levels among vaccinated individuals and evidence of breakthrough infections over a course of time. With an emerging science behind the need for COVID-19 vaccine booster shots, there equally is a contrasting idea regarding its absolute necessity.